Regular maintenance appointments after non‐surgical scaling and root planing support periodontal health in patients with or without dry mouth: A retrospective study. Issue 5 (20th January 2021) - Sparrow, Taylor V.; Fritz, Peter C.; Sullivan, Philip J.; Ward, Wendy E.
Abstract: Objective: Non‐surgical scaling and root planing (SRP), as an initial form of periodontal treatment, followed by ongoing periodontal maintenance appointments is necessary to manage periodontal disease and prevent tooth loss. Saliva also has an essential role in oral health though the relationship between low salivary flow and periodontal outcomes has not been extensively investigated. This study determined if patients with dry mouth have similar clinical outcomes as patients without dry mouth when receiving regular periodontal maintenance after SRP. Materials and methods: This is a retrospective study that investigated clinical periodontal outcomes in patients with ( n = 34) or without ( n = 85) dry mouth who had undergone SRP 1 to 5 years prior and had routine periodontal maintenance. The presence of dry mouth was established based on a patient's unstimulated salivary flow rate. Results: Probing depth for both patients with or without dry mouth was similar between groups and maintained 1 to 5 years following initial SRP. Improved probing depth achieved post‐SRP was sustained regardless of dry mouth status. Conclusion: Patients with or without dry mouth did not exhibit different probing depths.